2018
DOI: 10.1016/j.neo.2018.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Intratumor Heterogeneity is a Complex and Early Event in the Development of Adult T-cell Leukemia/Lymphoma

Abstract: The clonal architecture of tumors plays a vital role in their pathogenesis and invasiveness; however, it is not yet clear how this clonality contributes to different malignancies. In this study we sought to address mutational intratumor heterogeneity (ITH) in adult T-cell leukemia/lymphoma (ATL). ATL is a malignancy with an incompletely understood molecular pathogenesis caused by infection with human T-cell leukemia virus type-1 (HTLV-1). To determine the clonal structure through tumor genetic diversity profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…31 Subsequently, clonal heterogeneity in ATL based on mutation profiles of cross-sectional, whole-exome sequencing samples has been monitored, and subclonal admixtures containing specific mutations have been proposed. 32 In the current study, we focused on developing an understanding of clonal architecture based on TCR profiles in ATL. To our knowledge, this is the first report of TCR clonal architecture in ATL using RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…31 Subsequently, clonal heterogeneity in ATL based on mutation profiles of cross-sectional, whole-exome sequencing samples has been monitored, and subclonal admixtures containing specific mutations have been proposed. 32 In the current study, we focused on developing an understanding of clonal architecture based on TCR profiles in ATL. To our knowledge, this is the first report of TCR clonal architecture in ATL using RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of ITH on drug resistance and targeted therapy strategies has been demonstrated using multiple-site profiling in solid tumors and is regarded as a paradigm shift in cancer care [ 42 ]. In contrast, only a limited number of studies addressed ITH in non-solid tumors [ 43 , 44 , 45 , 46 ]. Wogsland et al studied intra- and inter-tumor heterogeneity of follicular lymphoma (FL), a B-cell malignancy, by using mass cytometry to obtain deep profiling of cell subsets [ 43 ].…”
Section: Intra-tumor Heterogeneity—the Challenge Of Treating “Many Cancers In One”mentioning
confidence: 99%
“…The diagnosis of primary and metastatic tumors is typically based on a single biopsy representing only a snapshot of ongoing tumor evolution and may be compromised by ITH [ 49 ]. The studies described above show that a sole biopsy does not accurately capture the tumor’s genetic and phenotypic heterogeneity [ 28 , 46 ]. Therefore, multimodal strategies have to be taken into account to ensure patients receive effective and targeted therapy.…”
Section: Integration Of Intra-tumor Heterogeneity Into Multi-layered Personalized Cancer Therapymentioning
confidence: 99%
“…This was first identified by Southern blot analysis of HTLV-1 provirus integration, and more recently by next-generation sequencing methods of integration sites (Yamaguchi et al, 1984; Gillet et al, 2011). Alternatively, variant allele frequency measurements of specific ATL genetic abnormalities provide an alternative measurement of clonal outgrowth of ATL (Farmanbar et al, 2018). Laydon et al (2014) and Farmanbar et al (2019) also reported quantification of HTLV-1 clonality using TCR diversity analysis.…”
Section: Biomarkers For Atlmentioning
confidence: 99%
“…However, we have identified subjects in whom two or more TCR gene rearrangements are present within a population of ATL cells with a single proviral integration site (Rauch et al, 2019). Moreover, intratumor heterogeneity has been shown to be a complex and early event in the development of ATL (Farmanbar et al, 2018).…”
Section: Biomarkers For Atlmentioning
confidence: 99%